Differential photothermal and photodynamic performance behaviors of gold nanorods, nanoshells and nanocages under identical energy conditions. (22nd January 2019) - Feng, Yanlin; Chang, Yun; Sun, Xiujuan; Cheng, Yan; Zheng, Runxiao; Wu, Xiaqing; Wang, Li; Ma, Xiaomin; Li, Xi; Zhang, Haiyuan
Abstract : The corner angle structure of Au nanostructures could more efficiently convert the photon energy into the photodynamic performance. Abstract : Various gold (Au) nanostructures have shown promising near infrared (NIR) light-activated phototherapeutic effects; however, their reported photothermal or photodynamic performance behavior is usually inconsistent or even conflicted, dramatically limiting the improvement of phototherapeutic Au nanostructures. The potential reason for this uncertainty is mainly because the photoactivities of Au nanostructures are not evaluated under identical energy conditions. Herein, three Au nanostructures, Au nanorods (NRs), nanoshells (NSs), and nanocages (NCs), were prepared to provide the same localized surface plasmon resonance (LSPR) peaks at 808 nm. All these Au nanostructures (at the same optical density) could fully exert their photoactivities under the identical and optimal energy conditions of 808 nm laser irradiation. It was found that these Au nanostructures could induce similar levels of temperature elevation but different levels of reactive oxygen species (ROS) production, where Au NCs exhibited the highest ROS production, followed by Au NSs and NRs. In vitro and in vivo phototherapeutic assessments further supported that Au NCs could cause the most severe cell death and tumor growth regression. This means that the identical incident energy has different contributions to the photothermal and photodynamic performance of Au nanostructures, and the corner angle structures of Au NCs compared with NSs and NCs could more efficiently convert the photon energy into photodynamic properties. Altogether, Au NCs hold great potential for phototherapy due to their efficient energy utilization capability.